Nest architecture and population dynamics of the Ponerinae ant, Ectatomma opaciventre Roger (Hymenoptera : Formicidae) - Antonialli-Junior, W. F.; Giannotti, E. (Assn Advan Zoology, 1997)
Eleven nests of Ectatomma opaciventre were collected from January to December, 1994, in Rio Claro, SP, southeastern Brazil. This species excavates their nests up to 68 cm deep, containing 3, 4 or 5 chambers. The hole of entrance has a chimney-like rigid structure, with up to 2/5 cm high. The most numerous colonies were found in January and February, with 47 and 62 adult ants, respectively. The quantity of individuals decreased from March, being observed colonies with only 9 adult ants in June and July. The colony population increased again since September. Reproductive forms (winged ants) were observed between October and February. We did not observed immature stages in July, but they were numerous between September and March. There was a significant correlation between the number of colony individuals and temperature, but not between the number of colony individuals and relative humidity and rainfall. E. opaciventre is a species of hunter ants which have not an efficient recruitment system for food collecting, consequently their colonies are small due to the scarcity of food resources during the colder and dry months.